Descriptive analysis of the Action Plan of Praia (2021) of CPLP - Delfino, Martina; Boganika, Luciane; Albuquerque, Davi (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2023)
The Community of Portuguese Language Countries (CPLP) was established in 1996. One of the main objectives of the CPLP is to promote internationally the Portuguese language. Since 2010, the CPLP has been publishing, every three years, an Action Plan, discussing activities and results to be achieved in the field of language promotion. In this article, the authors aim to elaborate a descriptive analysis of the last Action Plan, redacted in 2021, in the city of Praia, Cape Verde. The analysis shed light on the impersonal, general, and incomplete nature of the policies outlined in the Action Plan which influence the policies implementation as well as any measuring process of their effectiveness. ———————————————————————————————————— ANÁLISE DESCRITIVA DO PLANO DE AÇÃO DE PRAIA (2021) DA CPLP A Comunidade dos Países de Língua Portuguesa (CPLP) foi criada em 1996 e tem como um dos seus objetivos promover e divulgar a língua portuguesa. Desde 2010, a cada três anos, a CPLP elabora um Plano de Ação para divulgar as próximas atividades e resultados que pretende alcançar. Neste artigo, temos como objetivo principal elaborar uma análise descritiva do último Plano de Ação, criado em 2021, na cidade de Praia, Cabo Verde. Nossas conclusões são que a maioria das ações propostas no Plano de Ação de Praia estão redigidas de forma impessoal, de maneira generalizada e não são detalhadas, o que torna difícil a construção de ferramentas para avaliá-las ou verificar se essas ações estão funcionando na prática. — Original em inglês.